2016
DOI: 10.3897/zookeys.603.9144
|View full text |Cite
|
Sign up to set email alerts
|

Conflict of mitochondrial phylogeny and morphology-based classification in a pair of freshwater gastropods (Caenogastropoda, Truncatelloidea, Tateidae) from New Caledonia

Abstract: Morphological classification and mitochondrial phylogeny of a pair of morphologically defined species of New Caledonian freshwater gastropods, Hemistomia cockerelli and Hemistomia fabrorum, were incongruent. We asked whether these two nominal species can be unambiguously distinguished based on shell morphology or whether the taxonomic discrepancy inferred from these character types was reflected in the variation of shell morphology. Our investigations were based on phylogenetic analyses of a fragment of the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The study suggests that genetic characters are determined by the distribution history of the species, whilst the shell structure to a greater extent reflects the influence of local environmental factors. This probably explains the fact that in some studies, GM-based analysis and molecular analysis showed similar results (Cruz et al, 2012;Vaux et al, 2018), whilst in others they did not (Becker et al, 2016).…”
Section: Shellsmentioning
confidence: 91%
See 2 more Smart Citations
“…The study suggests that genetic characters are determined by the distribution history of the species, whilst the shell structure to a greater extent reflects the influence of local environmental factors. This probably explains the fact that in some studies, GM-based analysis and molecular analysis showed similar results (Cruz et al, 2012;Vaux et al, 2018), whilst in others they did not (Becker et al, 2016).…”
Section: Shellsmentioning
confidence: 91%
“…The main fields of application include the study of intraspecific variability (Vuolo et al, 2011;Madeira et al, 2012;Moneva et al, 2012b;Sepúlveda and Ibáñez, 2012;Vogler et al, 2012;Avaca et al, 2013;Camama et al, 2014;Jamasali et al, 2014;Sobrepeña and Demayo, 2014;Cazenave and Zanatta, 2016;Zhao et al, 2019;Tuset et al, 2020) and assessment of environmental impacts (Sepúlveda and Ibáñez, 2012;Vogler et al, 2012;Vasallo et al, 2013;Camama et al, 2014;Cazenave and Zanatta, 2016;Amini-Yekta et al, 2019;Zhao et al, 2019), including the effect of pollution (Márquez et al, 2011;Abdelhady, 2016;Primost et al, 2016). Nevertheless, GM was also used for identification of mollusks (Doyle et al, 2018), evaluation of interspecific variability (Dommergues et al, 2003;Carvajal-Rodríguez et al, 2005;Vuolo et al, 2011;Cruz et al, 2012;Vogler et al, 2012;Silos et al, 2014;Becker et al, 2016;Miller, 2016), ontogenetic and individual variation (Moneva et al, 2012a;Avaca et al, 2013;Sobrepeña and Demayo, 2014), and to characterize phylogenetic relationships (Smith and Hendricks, 2013;Dillon and Jacquemin, 2015;…”
Section: Shellsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, molecular studies indicated a position within the Tateidae (Wilke et al 2013), a much smaller family with 32 genera, distributed in Australasia/Oceania and the Neotropics (Wilke et al 2013, Haase andZielske 2015). Considering the possibility of conflict with molecular phylogenies and morphologybased classifications, as recently shown for some Tateidae (Becker et al 2016), we choose not to take any position regarding the familial status of Potamolithus until all the evidence corroborates one of these, or different, taxonomic hypotheses. Comparisons are made with other subterranean truncatelloids.…”
Section: Introductionmentioning
confidence: 99%